Parallelized Kalman Filters for Mitigation of the Excess Phase Noise of Fast Tunable Lasers in Coherent Optical Communication Systems - Fan Liu; Yi Lin; Yonglin Yu; Liam P. Barry (IEEE Photonics Journal, 2018)
Numerical and experimental investigations are carried out on the performance of parallelized Kalman filters applied for mitigation of the excess phase noise of fast tunable lasers. Based on the characterization of the phase noise of a sampled grating distributed Bragg reflector (SG-DBR) laser, the proposed carrier phase recovery (CPR) scheme using Kalman filters is introduced. By performing simulations of data transmission with various advanced modulation formats in the presence of the excess phase noise, the Kalman filter based CPR scheme shows its ability to overcome the excess phase noise and this method is suitable for parallel processing. Then the results are further demonstrated by 12.5 Gbaud QPSK and 16-QAM transmission experiments employing the SG-DBR laser. We find that the Kalman filters have better performance than the 2nd-order phase-locked loop in parallel systems due to a better phase noise tolerance. The bit error rate performance is also examined in the whole tuning range (∼30 nm) of the tunable laser, which further proves the feasibility of the proposed scheme.